On the Application of Continuity Condition in the Volume-Surface Integral Equation for Composite Closed PEC-Electrical Anisotropy Objects - Jinbo Liu; Zengrui Li; Jiming Song; Limei Luo, (Applied Computational Electromagnetics Society Journal (ACES), 2019)
The validity of the use of continuity condition (CC), combined with the volume-surface integral equation (VSIE), is studied when it is explicitly enforced on the closed perfect electric conductor (PEC)-electrical anisotropy interfaces. It is found that if the standard magnetic field integral equation (MFIE) is involved in the VSIE to model the closed PEC surfaces, the solution might be inaccurate, especially when the CC is enforced. The reason for this phenomenon is discussed, and two previously reported approaches are adopted to improve the accuracy of MFIE. Numerical results show that whether the CC is enforced or not, the improvement of the MFIE will result in more accurate VSIE solution.